The Social Media Marketing Effect On Brand Awareness And Brand Loyalty In Lasik Clinic Jakarta, Indonesia - Frizky Ramadhan; Tantri Yanuar Rahmat Syah; Mohamad Reza Hilmy; Rokiah Kusumapradja (Journal of Multidisciplinary Academic, 2020)
The number of internet users in Indonesia has increased every year reached 18.9% of 171.17 million Indonesians have accessed social media services. Social media is known to be a place for effective and efficient promotion. Thus, the one of clinics namely Lasik Clinic is operating in the field of Lasik surgery. Founded in 2017, only less than 20% of new patients knew the clinic through social media. Social media marketing (SMM) is a marketing process through social media platforms. Brand awareness (BA) is the ability of customers to remember a brand. Brand loyalty (BL) is a measure of the customer's relationship to a brand. Social media marketing is known to increase BA and BL. Thus, in this study study aims to analyze the effect of SMM on BA and BL of the clinic. Data collection was carried out using questionnaires on 100 patients and families which is the data performed validity and reliability tests. Here, data analysis was processed using the SEM LISREL method. The results of the data description obtained SMM, BA, BL on the questionnaire included in the high category with each value 82.14%, 81.87%, and 84.73%. The results of data analysis showed that there was a significant influence between SMM on BA (T = 5.13) and BL (T = 4.74) which was in accordance with some previous studies whereas BA had no significant effect on BL (T = 1.72) which not in accordance with previous research. This may be caused by other factors not examined in this study.